The Impact of Social Media on Language Learning - qizi, Abdullayeva Durdona Sobirjon (Journal of Innovation in Education and Social Research, 2024)
As social media has become a daily part of our lives, its impact on language learning is significant. This article investigates how social media affects language learning, covering both the positives and challenges of its integration into education.